Functional assessment of the glycoproteins of a novel Hendra virus variant reveals contrasting fusogenic capacities of the receptor-binding and fusion glycoproteins - Andrew Z. Ma; Yao Yu Yeo; Jean F. Lee; Colin M. Kim; Shahrzad Ezzatpour; Carolina Menchaca; Viraj Upadhye; Edward J. Annand; John-Sebastian Eden; Raina K. Plowright; Alison J. Peel; David W. Buchholz; et al. (mBio)
ABSTRACT A novel Hendra virus (HeV) genotype (HeV genotype 2 [HeV-g2]) was recently isolated from a deceased horse, revealing high-sequence conservation and antigenic similarities with the prototypic strain, HeV-g1. As the receptor-binding (G) and fusion (F) glycoproteins of HeV are essential for mediating viral entry, functional characterization of emerging HeV genotypic variants is key to understanding viral entry mechanisms and broader virus-host co-evolution. We first confirmed that HeV-g2 and HeV-g1 glycoproteins share a close phylogenetic relationship, underscoring HeV-g2’s relevance to global health. Our in vitro data showed that HeV-g2 glycoproteins induced cell-cell fusion in human cells, shared receptor tropism with HeV-g1, and cross-reacted with antibodies raised against HeV-g1. Despite these similarities, HeV-g2 glycoproteins yielded reduced syncytia formation compared to HeV-g1. By expressing heterotypic combinations of HeV-g2, HeV-g1, and Nipah virus (NiV) glycoproteins, we found that while HeV-g2 G had strong fusion-promoting abilities, HeV-g2 F consistently displayed hypofusogenic properties. These fusion phenotypes were more closely associated with those observed in the related NiV. Further investigation using HeV-g1 and HeV-g2 glycoprotein chimeras revealed that multiple domains may play roles in modulating these fusion phenotypes. Altogether, our findings may establish intrinsic fusogenic capacities of viral glycoproteins as a potential driver behind the emergence of new henipaviral variants.IMPORTANCEHeV is a zoonotic pathogen that causes severe disease across various mammalian hosts, including horses and humans. The identification of unrecognized HeV variants, such as HeV-g2, highlights the need to investigate mechanisms that may drive their evolution, transmission, and pathogenicity. Our study reveals that HeV-g2 and HeV-g1 glycoproteins are highly conserved in identity, function, and receptor tropism, yet they differ in their abilities to induce the formation of multinucleated cells (syncytia), which is a potential marker of viral pathogenesis. By using heterotypic combinations of HeV-g2 with either HeV-g1 or NiV glycoproteins, as well as chimeric HeV-g1/HeV-g2 glycoproteins, we demonstrate that the differences in syncytial formation can be attributed to the intrinsic fusogenic capacities of each glycoprotein. Our data indicate that HeV-g2 glycoproteins have fusion phenotypes closely related to those of NiV and that fusion promotion may be a crucial factor driving the emergence of new henipaviral variants.